CURRENT ISSUES IN TEACHING THE RUSSIAN LANGUAGE - Diyorova Nargiza Omonovna (Ecominds Press, 2025)
This article discusses modern problems encountered in the process of teaching the Russian language. It discusses the problems of students' motivation for the language, the insufficient use of modern pedagogical technologies, the quality of educational resources and the qualification of teachers. It also presents innovative approaches, interactive methods and recommendations for creating a language environment as solutions to the problems.
Keywords: Russian language, teaching problems, modern education, motivation, pedagogical technologies, language environment, interactive methods.